The Effect of Towel Toe Curl Exercise and Tibialis Posterior Strengthening on Dynamic Balance of Flatfoot Patients at SD Negeri 104242 Lubuk Pakam - Jehaman, Isidorus; Telaumbanua, Gres Indah Kasih; Raynald Ignasius Ginting; Redi Tantangan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Improper use of the foot can cause problems when walking and even endanger a person's health. The arch of the foot helps withstand impact pressure and provides stability when standing or walking. Flatfoot is a deformity related to the foot, such as medial longitudinal arch disorders of the foot, valgus deformity of the heel, and forefoot abduction. The exercise methods that can be given to overcome flatfoot are Towel toe curl exercise and tibialis posterior strengthening. Purpose: to improve foot function by strengthening the intrinsic muscles of the foot. While tibialis posterior strengthening exercise is to strengthen the tibialis posterior muscle, which is part of the extrinsic muscle. Research method: This type of research is quantitative with a one group pre-test and post-test design. Data analysis using paired sample t-test. The sample of this study were children at SD Negeri 104242 Lubuk Pakam who suffered from flatfoot with a total of 22 samples. The intervention given was towel toe curl and tibialis posterior strengthening 3 times a week for 4 weeks with a total of 12 actions. Before the dynamic balance intervention, respondents were measured first (pretest) with the Y Balance Test (YBT) and re-measured after the intervention (Posttest). Results and discussion: The results of the paired sample t-test obtained a significant value (p) of 0.000, greater than the alpha value (a) (0.000 <0.05), meaning that there is a significant effect of towel toe curl exercises and tibialis posterior strengthening on improving dynamic balance in flatfoot children. Conclusion: Based on the results of the study, it can be concluded that towel toe curl exercises and tibialis posterior strengthening can be one of the training methods that can be applied to overcome dynamic balance disorders in flatfoot sufferers